The mediating role of math self-efficacy between school-based parental involvement and math performance among students in Southeast Asia: evidence from PISA 2022 - Djekourmane, Denis; Zhang, Yang; Zhang, Xue; Wang, Zhiyuan (Frontiers in Psychology, 2025)
This study aims to investigates the relationship between school-based parental involvement and student math performance by examining the mediating role of student math self-efficacy in six top-performing countries and economies in Southeast Asia. Leveraging the subset data of 28,189 respondents from the Programme for International Student Assessment (PISA) 2022 and STATA version 15.1 software, we utilize partial least-squares structural equation modeling (PLS-SEM) to test the relationship. The results reveal significant positive correlations between school-based parental involvement, student math performance, and student math self-efficacy. Moreover, student math self-efficacy has a positive direct impact on student math performance. The study also finds that student math self-efficacy played a positive mediating role in the relationship between school-based parental involvement and student math performance. Based on the above findings, the study suggests that, to optimize math success, educational practices should not only foster school-based parental involvement but also create environments that foster student self-efficacy in mathematics. Further, the study emphasizes the importance of the cultural and Confucian heritage of education in Southeast Asia for contextual understanding. This approach provides a contextual cultural lens for understanding the relationship between school-based parental involvement and student math outcomes within the global for comparative interest towards student math skills. This study offers insightful theoretical and practical implications for policymakers, parents, educators, and researchers from regional and global perspectives.